Birthday - Suzuki, Koji; Meimu; Kokubo, Naomi; Hoffman, Steven; Lacuna, Wilbert (Milwaukie, OR : Dark Horse Manga, 1999)
Manga adaptation of Koji Suzuki$1 (Bs novel depicting the horror of cursed videotapes.s
English translation of the Japanese manga.
Keywords: Horror fiction; Manga; Japanese literature $v Comic books, strips, etc